1993
DOI: 10.1007/bf00021523
|View full text |Cite
|
Sign up to set email alerts
|

Deletion analysis of a 2S seed storage protein promoter of Brassica napus in transgenic tobacco

Abstract: The promoter and upstream region of the Brassica napus 2S storage protein napA gene were studied to identify cis-acting sequences involved in developmental seed-specific expression. Fragments generated by successive deletions of the 5' control region of the napA gene were fused to the reporter gene beta-glucuronidase (GUS). These constructs were used to transform tobacco leaf discs. Analyses of GUS activities in mature seeds from the transformed plants indicated that there were both negatively and positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 49 publications
5
78
1
Order By: Relevance
“…1) targeted at the FAD2 ⌬12-desaturase gene. All three constructs used the rapeseed (Brassica napus) napin promoter (Stalberg et al, 1993), which directs high-level transcription of the transgenes specifically in the embryo and endosperm of the developing Arabidopsis seed. A proportion of plants transformed with each construct produced seed with significantly reduced ⌬12 desaturation levels, and there were noticeable differences in effectiveness among the three constructs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) targeted at the FAD2 ⌬12-desaturase gene. All three constructs used the rapeseed (Brassica napus) napin promoter (Stalberg et al, 1993), which directs high-level transcription of the transgenes specifically in the embryo and endosperm of the developing Arabidopsis seed. A proportion of plants transformed with each construct produced seed with significantly reduced ⌬12 desaturation levels, and there were noticeable differences in effectiveness among the three constructs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This fragment is a 5Ј-truncated version of the full FAD2 coding region and was used to prevent any overexpression that might otherwise result from the sense transcription and translation of the full coding region. Expression was directed to the developing seeds by driving the constructs with the truncated version (Fp1) of the seed-specific napin promoter from rapeseed (Brassica napus; Stalberg et al, 1993). Three types of gene-silencing constructs were evaluated: a CS construct consisting of the 1,103-bp coding region fragment and its complete 3Ј-UTR (Fig.…”
Section: Gene-silencing Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are differences during seed development. At the heart stage, napin is expressed in the cotyledons but not in the embryonic axis, and at the torpedo stage, napin is expressed more strongly in the cotyledons than in the embryonic axis (Stålberg et al, 1993). It has been suggested that, for wild-type C. sativa, DGAT1 activity is strongest in the cotyledons, whereas PDAT is more important in the embryonic axis than in the cotyledons .…”
Section: Spatial Distribution Of Lipidsmentioning
confidence: 99%
“…Previous studies on the napA promoter indicated that the sequences between 2152 and +44 are essential for the seed-specific expression pattern in transgenic tobacco plants, and several ciselements upstream from 2152 were found to act as positive or negative regulatory motifs (Stålberg et al, 1993;Ellerströ m et al, 1996). We made similar napA promoter GUS reporter constructs that were stably transformed into Arabidopsis plants.…”
Section: Modification and Characterization Of Seed-specific Promotersmentioning
confidence: 99%